Closing the Winter Gap: An Evaluation of Somerville Winter Mobile Farmers' Market. - Marina, Sarah.; Blum, Janaki.; Bettisworth, Caitlin. (Tufts University. Tisch Library., 2018)
2014 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Groundwork Somerville. This project is part of the Office of Sustainability Student Project Database, a place to share and view student projects related to sustainability and the environment.